2008
DOI: 10.1074/jbc.m707362200
|View full text |Cite
|
Sign up to set email alerts
|

Human HDAC7 Harbors a Class IIa Histone Deacetylase-specific Zinc Binding Motif and Cryptic Deacetylase Activity

Abstract: Histone deacetylases (HDACs) are protein deacetylases that play a role in repression of gene transcription and are emerging targets in cancer therapy. Here, we characterize the structure and enzymatic activity of the catalytic domain of human HDAC7 (cdHDAC7). Although HDAC7 normally exists as part of a multiprotein complex, we show that cdHDAC7 has a low level of deacetylase activity which can be inhibited by known HDAC inhibitors. The crystal structures of human cdHDAC7 and its complexes with two hydroxamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
259
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(271 citation statements)
references
References 49 publications
8
259
0
1
Order By: Relevance
“…1, is the first FDA-approved pan-HDACi to enter the clinic 10 as a treatment for cutaneous T-cell lymphoma. Crystal structures of human HDAC's with SAHA bound [11][12][13] show the hydroxamic acid coordinated to the active-site zinc (Zn) ion. Several HDACi's have thus been designed based on these data in which their structural motif consists of a metal binding group, a linker domain (that mimics the C a functional group of lysine) that occupies the enzyme's narrow channel and a cap group which interacts with residues on the enzyme surface.…”
mentioning
confidence: 99%
“…1, is the first FDA-approved pan-HDACi to enter the clinic 10 as a treatment for cutaneous T-cell lymphoma. Crystal structures of human HDAC's with SAHA bound [11][12][13] show the hydroxamic acid coordinated to the active-site zinc (Zn) ion. Several HDACi's have thus been designed based on these data in which their structural motif consists of a metal binding group, a linker domain (that mimics the C a functional group of lysine) that occupies the enzyme's narrow channel and a cap group which interacts with residues on the enzyme surface.…”
mentioning
confidence: 99%
“…[5][6][7] To date, detailed biostructural information is available only regarding a few among the known 11 metallo-enzymes. 1,[8][9][10][11] Consequently, the design of isoform-and class-selective inhibitors is somewhat arbitrary and derivative. 1,7,[12][13][14] In addition, complete data regarding the factual HDAC profile for most of the early discovered agents are not available, since the development of effective isozyme-based assays is relatively recent.…”
mentioning
confidence: 99%
“…No significant difference was found between the racemic 2 and its individual enantiomers, which proved to be equipotent against all of the zincdependent HDACs. To gain more insight into this equivalence, a docking analysis of the individual enantiomers of 2 was performed based on the crystal structures of HDAC8 8 and HDAC7, 9 which were chosen as representatives of class I and II HDACs, respectively ( Figure 2). 28 In binding these isoforms, a T-shape arrangement was observed for both enantiomers of ligand 2, which projected its aromatic motifs out from the active site channel toward lipophilic pockets located in opposite directions on the enzyme surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Kao et al also denoted that both HDAC5 and HDAC7 possess multiple repressor domains. The crystal structure of human HDAC7 confirmed that these repressor domains have intricate protein-protein interactions that could modulate its relatively weak deacetylase activity (65). Like HDAC7, full-length HDAC9 is known to colocalize and coimmunoprecipitate with NCoR repressor subunits (61).…”
Section: Complexity Of Complexesmentioning
confidence: 81%